Abnormalities in Pattern of Lateralization in Relation to Visuospatial Short Term Memory in Children with Williams Syndrome. (20th March 2014) - Chasouris, Antonios; Mayer, Peter; Stuart-Hamilton, Ian; Graff, Martin; Workman, Lance
Abstract : Williams syndrome (WS) is a genetic disorder characterised by significant intellectual disability. Initial studies indicate that children with WS have a profound bias for information in the top left of visual arrays. Study 1, using a visuospatial memory test for items presented in a3 × 3 matrix, found a significant top left bias in WS children relative to controls. Study 2 used a probe-based memory test with arrays in which items appeared with equal probability in each position. Relative to controls, WS children showed a significant top and left bias. In Study 3, the same children engaged in a visual search task and again, a top and left bias was found in the WS group. It is concluded that children with WS display atypical laterality, which might be explained by abnormal saccadic movements, by abnormalities involving development of the dorsal stream or by uneven cortical development.